(3efgL GdSGdc Edi CdajI GHf eGdcs - (3fhQ GdOjf CHi GdMSf Ydj Hf eMeO GdCTehfis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3BNQgG (B:s
(3Chd HGH GdfOGA dCHi MjGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B17 - (3U (B399 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B153s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeY GdTjN (B(54) s
Keywords: (3GdfMhs